Pengaruh Latihan Passing Diamond Dan Passing Triangle Terhadap Keterampilan Passing Pemain Sepakbola Ssb Psp Bangko - M Aulia Dafitra; Wilda Welis; Hadi Pery Fajri; Ridho Bahtra (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The problem of this research is the lack of passing accuracy in players and the monotonous variety of exercises that result in PSP Bangko SSB players getting bored. The purpose of this study is to find out the extent of the effectiveness of diamond passing and passing triangle exercises in SSB PSP Bangko. This type of research is pseudo-experimental research. This research was conducted on March 22 - June 7, 2021, conducted in the field of Koni Masurai Bangko Merangin Regency. The population of PSP BANGKO SSB players consists of 85 players. As for the way in determining samples, researchers use purposive sampling methods. The samples in this study were as many as 20 players. Based on the analysis of data in this study using t-test. The results of data processing in this study are thitung on passing diamond skills (8.6) > ttabel (2,262) and thitung on passing triangle skills (9) > ttabel (2,262) after being treated. Means There is a significant influence form of diamond passing and passing triangle training terhadap passing skills SSB PSP BANGKO football players.